1988
DOI: 10.1007/bf00179325
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1 and alpha-2 adrenoceptor agonists induce vasoconstriction of the normotensive rat caudal artery in vitro by stimulation of a heterogeneous population of alpha-1 adrenoceptors

Abstract: Although alpha-2 adrenoceptor agonists rapidly induce arterial vasoconstriction in vivo, such responses have proven difficult to obtain in vitro. We have investigated the vasoconstrictor effects of various alpha-1 and alpha-2 adrenoceptor agonists in the perfused superfused caudal artery of the normotensive rat. Intrinsic activities were; methoxamine; 1, phenylephrine; 0.94, noradrenaline; 0.93, guanfacine; 0.88, clonidine; 0.47, UK 14,304 [5-bromo-6-(2-imidazoline-2-ylamino)-quinoxaline tartrate]: 0.10, azepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The tissues were exposed to each concentration for 5 min, followed by a washout period during which the tension returned to the baseline value before addition of the next concentration of agonist. In tail artery, the pA 2 for the α 1 ‐adrenoceptor‐selective antagonist prazosin in antagonizing the effects of phenylephrine and methoxamine is in the range 9–9.5 (Abel and Minneman, 1986; Atkinson et al. , 1988) and, in preliminary experiments, we ascertained that the pA 2 for the α 2 ‐adrenoceptor‐selective antagonist rauwolscine in antagonising the effects of clonidine is ∼9.…”
Section: Methodsmentioning
confidence: 88%
“…The tissues were exposed to each concentration for 5 min, followed by a washout period during which the tension returned to the baseline value before addition of the next concentration of agonist. In tail artery, the pA 2 for the α 1 ‐adrenoceptor‐selective antagonist prazosin in antagonizing the effects of phenylephrine and methoxamine is in the range 9–9.5 (Abel and Minneman, 1986; Atkinson et al. , 1988) and, in preliminary experiments, we ascertained that the pA 2 for the α 2 ‐adrenoceptor‐selective antagonist rauwolscine in antagonising the effects of clonidine is ∼9.…”
Section: Methodsmentioning
confidence: 88%
“…It has been shown previously that the caudal artery of rat contains functional a 2 -adrenoceptors (Medgett & Langer, 1984;Atkinson et al, 1988). Although these post-junctional a 2adrenoceptors may play a prominent vasoconstrictor role in vivo (Redfern et al, 1995), when assayed in vitro, they contract tissue only when basal tension is elevated by prior application of another spasmogen (Templeton et al, 1989;MacLean & McGrath, 1990).…”
Section: Discussionmentioning
confidence: 97%
“…Smooth muscle contraction induced by a-adrenoceptor agonists in rat aorta is mostly if not exclusively mediated by aladrenoceptors (Ruffolo, 1985). Nevertheless, some (Weiss et al, 1983;Vila et al, 1993) but not all (Atkinson et al, 1988) studies have suggested that a, and a2-adrenoceptors are present in rat tail artery. Thus, in our experimental protocol, yohimbine (0.1 jIM) was present to prevent the stimulation of a2-adrenoceptors by agonists.…”
Section: Discussionmentioning
confidence: 99%